Implementation of the Plate Meal Method towards Self-Management of Type 2 Diabetes Mellitus Patients: Plate Meal Method toward Self-management on Diabetes Mellitus Type 2 - Rauza Alda; Riyan Mulfianda; Nanda Desreza (WMJ (Warmadewa Medical Journal), 2024)
Plate meal is a diet therapy program for Diabetes Mellitus Type 2 patients, which may balance the blood glucose by dividing food on the plate. Improving patient self-management may difference the patients, especially those with Diabetes Mellitus type 2. This research aimed to determine the difference of the plate meal method with diet program implementation toward self-management among patients with Diabetes Mellitus type 2. This research was a quasi-experiment with pre and post-test equivalent control group methods. The population of this research was thirty patients with Diabetes Mellitus type 2 in Ulee Kareng Regional Technical Implementation Unit Health Community Center of Banda Aceh, which was divided into two groups, consisting of 15 respondents from the intervention group and 15 from the control group. The technique used in taking the samples was purposive sampling. This research was conducted in Ulee Kareng Regional Technical Implementation Unit Health Community Center from June 19 to 27, 2023. The data analysis used was a paired t-test and an independent t-test. The result of the research showed that the p-value of the paired t-test on the intervention group was 0.002. Therefore, there was a difference. The p-value of the control group was 0.369, which showed that there was no difference toward the control group, while the p-value of the independent t-test was 0.047 (p-Value ? 0,05), indicating that there was an difference between the intervention and control group after the treatment of the intervention group. The conclusion of this study is that there is a difference in the application of the plate meal method diet program towards self-management in Type 2 DM patients at the UPTD Ulee Kareng Community Health Center, Banda Aceh between the control and treatment groups.